ERROR ANALYSIS ON LEARNERS’ PASSIVE SENTENCES - J Sutomo (Universitas Stikubank (UNISBANK) Semarang, 2010)
This study focuses on error analysis on passive sentences of the third semester students of the FBIB (the Faculty of Language and Cultural Studies) of Unisbank, in the academic year 2009/2010. They consist of three classes with the total number of students 65. Therefore, the number of the data collected was 65, each consisted of 10 passive sentences. The writers took 20 data (30.76%) randomly, so the total number of passive sentences to be analyzed was 200. Five types of errors were identified on a sentence level, namely: (1) omission, (2) over conclusion, (3) misformation, and (4) misordering, and (5) Blends. The findings show that the misformation error is of the highest occurrence: 42.35%. The results will be of benefit for material development in the FBIB of Unisbank. Keywords: error, omission, over conclusion, misformation, misordering, blends.